2005
DOI: 10.1021/bi050261r
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Loop Effects on the Free Energy Change of Redox and pH-Dependent Equilibria in Cupredoxins Probed on Amicyanin Variants

Abstract: In this work, we have determined the thermodynamic parameters of the reduction of four different variants of Thiobacillus versutus amicyanin by electrochemical techniques. In addition, the thermodynamic parameters were determined of the low-pH conformational change involving protonation of the C-terminal histidine ligand and the concomitant dissociation of this histidine from the Cu(I) ion. In these variants, the native C-terminal loop containing the Cys, His, and Met copper ligands has been replaced with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 64 publications
3
42
0
Order By: Relevance
“…Similar behavior has been observed in plastocyanin (25,26), pseudoazurin (27,28), and AMI (21,22,29) and is thought to have physiological relevance (26,29). Loop mutation experiments have shown that, in most cases, lengthening the ligand-containing loop lowers the His ligand pK a (9,10,12,38), whereas loop contraction increases the value (8,11,12). In AZ, the His-117 ligand does not protonate in the accessible pH range, and a pK a of Ͻ2 has been calculated (20).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Similar behavior has been observed in plastocyanin (25,26), pseudoazurin (27,28), and AMI (21,22,29) and is thought to have physiological relevance (26,29). Loop mutation experiments have shown that, in most cases, lengthening the ligand-containing loop lowers the His ligand pK a (9,10,12,38), whereas loop contraction increases the value (8,11,12). In AZ, the His-117 ligand does not protonate in the accessible pH range, and a pK a of Ͻ2 has been calculated (20).…”
Section: Discussionsupporting
confidence: 60%
“…Further shortening of the loop leads to an additional increase in the pK a . The structures of AZAMI and AZAMI-F demonstrate that their active-site structures, including hydrogen-bonding patterns, are very similar, and, thus, His ligand protonation must be influenced by the length of the loop [probably an entropic effect (38,39)]. The increase in the pK a of the His ligand upon shortening this loop results in a value closer to physiological pH and is, thus, more likely to have a functional role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since reduction thermodynamics for metalloproteins in aqueous solution are deeply affected by solvent reorganization phenomena [21][22][23][24][25][44][45][46], the thermodynamic data listed in Table 1, as such, cannot be used to extract information on mutation-induced proteinbased effects on the thermodynamics of Fe(III) to Fe(II) reduction. In particular, it is worthy of note that for all the present KatG variants the mutation-induced changes in ΔH°′ rc and ΔS°′ rc are much larger than the corresponding changes in ΔG°′ rc , and therefore in E°′ (Table 1).…”
Section: Ferric To Ferrous Transition Of Wild-type Synechocystis Katgmentioning
confidence: 99%
“…In particular, it is worthy of note that for all the present KatG variants the mutation-induced changes in ΔH°′ rc and ΔS°′ rc are much larger than the corresponding changes in ΔG°′ rc , and therefore in E°′ (Table 1). This is typical of the presence of enthalpy-entropy compensation phenomena occurring within a series of homologous species subjected to the same reaction at fixed temperature [21,22,[42][43][44][45][46][47][48], according to Eq. (1) [45][46][47][48]:…”
Section: Ferric To Ferrous Transition Of Wild-type Synechocystis Katgmentioning
confidence: 99%